Digitalization Accounting for MSMEs in Indonesia : A Literature Review - Irma Hidayati; Sudarmiatin Sudarmiatin; Agus Hermawan (Cita Konsultindo Research Center, 2023)
This study seeks to examine trends, developments, and prospects for future research on digitalization accounting for MSMEs in Indonesia. This study used a systematic literature review, finding 20 articles from 2018-2023. Two sections comprise the findings of this investigation; the first section discusses research trends divided into four categories (theme, theories, methods of study, and fundamental data analysis techniques) and the current state of research. Second, evaluate future study opportunities. The following are five categories of study suggestions: cloud computing, digital accounting, accounting system information implementation, and point of sale.